Research Article Introductions: Variations Across Disciplines and Cultures - Ryvitytė, Birutė (Kalbotyra, 2003)
The purpose of this study is to look at introductions across disciplines and cultures and to investigate whether differences across academic disciplines are more noticeable than cross-cultural differences. The material of the present study consists of a sample of 60 introductions, i.e. 20 each from Medicine, Economics and Linguistics, 30 in English and 30 in Lithuanian. The model of analysis was developed from Swales’ CARS model (Swales 1990). The findings reveal certain preferences of textual patterns by the three disciplines common to both English and Lithuanian academic traditions as well as some cultural differences.